Obtention of ethyl lactate using process intensification: Simulation, optimization, and control using a reactive divided wall distillation column (2020)
ABSTRACT: The implementation of a chemical process must enforce the development of solvents that are environmentally liable, considering the economic and safety factors. In that way, process intensification extends the possibility to adapt conventional processes to reroute a feasible production of these solvents. The sustainability development in separation-reaction processes associates higher energy efficiency and pollutant reduction. This work proposes to Minimize the number of units required in a conventional process, including separation and Reactions, initially through a shortcut method of the analysis of the statics, to generate a feasible reactive distillation flowsheet. Then, rigorous simulations state the condition of the process, Including the kinetic subroutine and the phase equilibria information, resulting in the generation of more sustainable designs, through the identification of the phenomena tasks in each unit, leads to the gradual intensification and bringing the final flowsheet alternatives. It shows the feasibility to intensify gradually a base case into an intensified process, keeping the production requirements with the improvement of economic and sustainability factors. Finally, two control structures schemes, composition, and temperature will present the transient behavior in a Reactive divided wall distillation column to synthesize ethyl lactate. All control structures include PI control loops to manipulate three variables, reflux flow, liquid split ratio, and the heat duty in the reboiler. To handle these variables is necessary to locate the controllers, two in the main column and the third in the prefractionator, showing that a temperature control structure has Better performance under flow and compositions perturbations.